A study of chromatin and rDNA transcription in Saccharomyces cerevisiae - Jones, H (2006)
Within the cell, DNA is compacted through its organisation into chromatin. A great deal is known about the chromatin structure of RNA Polymerase II-transcribed loci and its impact on transcription by this polymerase. In contrast, far less is known about the role of chromatin in RNA Polymerase I transcription. RNA Polymerase I transcribes rDNA genes within the nucleolus, producing 60% of all cellular transcripts. Studies into the chromatin structure of the rDNA locus have resulted in an unclear picture as to the nature of chromatin on actively transcribed rDNA genes. Furthermore, chromatin remodeling factors have so far only been shown to function on inactive rDNA repeats. This study used a combination of techniques to investigate the chromatin structure of actively transcribed rDNA repeats. In addition, the presence and function of chromatin remodeling factors at this locus was addressed. Chromatin immunoprecipitation analysis revealed that actively transcribed rDNA genes possess a form of chromatin structure composed of, at least, histones H2B and H3 and that histone H3 is dimethylated at lysine 4 and 36. Furthermore, chromatin remodeling factors Chd1p, Isw1p and Isw2p are present across the rDNA locus and are likely recruited by both histone tail modifications and rRNA. In vivo chromatin analysis was used to analyse the chromatin structure over the termination region of rDNA repeats and showed that Chd1p, Isw1p and Isw2p function redundantly to maintain a specific chromatin structure at inactive repeats. Finally, transcription run-on analysis demonstrated that Chd1p, Isw1p and Isw2p function redundantly to ensure efficient transcription. These data therefore lead to an updated model of S. cerevisiae rDNA transcription, whereby RNA Polymerase I transcription occurs on a chromatin template. Chromatin modifications function to recruit chromatin remodeling factors that are required to ensure efficient transcription.